China in Africa: Competitor of the EU? - Joachim Ahrens; Katja Kalkschmied (OrdnungsPolitisches Portal (OPO), 2021)
European development strategies with Africa have been challenged by a pragmatic, self-interested Sino-African trade and development cooperation with a focus on infrastructure projects, which gained momentum in the last twenty years. African-European development cooperation and European norms and standards as role models appear to have lost some of their appeal to African governments due to incoherencies, poor communication, and inadequate deliberations. Recent changes in European development strategies with Africa do not go far enough to solve these issues to stop a gradual shift in development cooperation away from Europe towards China. In this article we discuss and contrast Sino-African relations with African-European relations and investigate whether there exists competition between China and EU in Africa and what opportunities and threats this competition may hold for Africa.
Keywords: 330; Development cooperation; Sino-African relations; European-African relations; competitionover Africa